STUDI OPTIMASI SISTEM PENCAHAYAAN RUANG KULIAH DENGAN MEMANFAATKAN CAHAYA ALAM - Irianto, Chaerul Gagarin (Jurnal Teknik Elektro, 2006)
A good lighting system has to meet three criteria; quality and quantity of light and efficient powerconsumption. A good lighting room will help effective activities inside the room. To achieve an optimumlighting, natural light has to be considered in the installation design. To optimise lighting installation ofthe building E classroom, clustering luminer with the switch has to proportionately adjust according tothe sun light incidence to the room.Keywords: quality and quantity of light, efficient power consumption, natural light, clustering luminer